Complete Resection of a Massive Synovial Osteochondromatosis of the Hip Using an Anterior Approach: A Report of Two Cases - Masanao Kataoka; Koji Goto; Yutaka Kuroda; Toshiyuki Kawai; Ouki Murata; Masayuki Sugimoto; Shuichi Matsuda (Case Reports in Orthopedics)
Arthroscopic excision of synovial osteochondromatosis of the hip is commonly performed. However, when the lesion extends to the extra-articular space of the hip joint, excision using arthroscopy becomes difficult. Although surgical dislocation of the hip with a trochanteric flip osteotomy is commonly used, manual access to the inferomedial portion of the acetabulum remains difficult. In this case report, we describe arthroscopic resection followed by open surgery using an anterior approach with or without surgical dislocation to excise a synovial osteochondromatosis of the hip that had extended to the extra-articular space and formed a herniation sac. Excision was completed without complications. An anterior approach with or without surgical dislocation should be considered as a surgical option for the treatment of a massive synovial osteochondromatosis of the hip joint.